Carbon emission in MINT economies : The role of poverty, population, energy use and economic factors - Bekun, Festus Victor; Uzuner, Gizem; Onifade, Stephen Taiwo; Alola, Andrew Adewale (John Wiley & Sons, 2024)
Poor environmental quality is usually observed in developing blocs. Some plausible explanations are due to the high poverty level and their economic characterisation. The present study focuses on exploring the effect of poverty on environmental degradation over annual data from 1990 to 2018 for MINT economies (Mexico, Indonesia, Nigeria, Turkiye). By leveraging panel econometrics procedures that are robust to cross-sectional and slope homogeneity issues, the results show evidence of an equilibrium relationship among the examined variables namely households final consumption expenditure, CO2 emissions, GDP, electricity consumption and population over the sampled period. Findings from this study establish that poverty is a core to environmental degradation in Türkiye and the plausible explanation is due to the country's demography while on the contrary, Nigeria, Indonesia and Mexico show that poverty is not a core contributor to environmental degradation. Thus, from a policy lens, there is need for concerted efforts by government officials and all stakeholders in the examined countries to reduce environmental degradation by improving per capita income (SDG-8) in the region productive economic activities to raise income level in the bloc. Additionally, there is a need for energy transition from fossil fuel-based energy to cleaner energy alternative options. More policy caveats are elucidated in the concluding section.
Keywords: fi=Taloustiede|en=Economics|